Relation between age, femoral neck cortical stability, and hip fracture risk. - Mayhew, P; Thomas, C; Clement, J; Loveridge, N; Beck, T; Bonfield, W; Burgoyne, C; Reeve, J (2005)
BACKGROUND: Hip fracture risk rises 100 to 1000-fold over 60 years of ageing. Loss of resistance to bending is not a major feature of normal ageing of the femoral neck. Another cause of fragility is local buckling or elastic instability. Bones adapt to their local experience of mechanical loading. The suggestion that bipedalism allows thinning of the underloaded superolateral femoral neck cortex arises from the failure of walking to transmit much mechanical load to this region. We aimed to measure whether elastic instability increases greatly with age since it might trigger hip fracture in a sideways fall. METHODS: We measured with computed tomography the distribution of bone in the mid-femoral neck of 77 proximal femurs from people who died suddenly aged 20-95 years. We then calculated the critical stress, from the geometric properties and density of the cortical zone most highly loaded in a sideways fall, as a threshold for elastic instability. FINDINGS: With normal ageing, this thin cortical zone in the upper femoral neck became substantially thinner. Relative to mean values at age 60 years, female cortical thickness declined by 6.4% (SD 1.1) per decade (p<0.0001), and critical stress by 13.2% (4.3) per decade (p=0.004) in the superoposterior octant compressed most in a sideways fall. Similar, but significantly smaller, effects were evident in men (p=0.004). This thinning compromised the capacity of the femur to absorb energy independently of osteoporosis. Patients with hip fracture had further reduced stability. INTERPRETATION: As women age, hip fragility increases because underloading of the superolateral cortex leads to atrophic thinning. Because walking does not sufficiently load the upper femoral neck, the fragile zones in healthy bones may need strengthening, for example with more well targeted exercise.